2007
DOI: 10.1371/journal.pone.0000166
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunisation to Donor Antigens and Immune Rejection Following Foetal Neural Grafts to the Brain in Patients with Huntington's Disease

Abstract: BackgroundThe brain is deemed “immunologically privileged” due to sparse professional antigen-presenting cells and lymphatic drainage, and to the blood-brain barrier. Although the actual extent of this privilege is controversial, there is general consensus about the limited need in intracerebral neural grafts for immunosuppressive regimens comparable to those used in other cases of allotransplantation. This has led over the past fifteen years to the use of either short-term or even no immunosuppression in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 14 publications
4
101
0
4
Order By: Relevance
“…Integration of grafted tissue without clinical improvement 1 C a p e t i a net al 14 Stem cells and neurological diseases S Gögel et al additional immunosuppressive therapy as antibodies against foetal donor antigens were detected in patient's blood samples. 10 Similar results have been obtained in a separate study initiated by Kopyov and colleagues in Los Angeles. Post-mortem examination, 6 years after transplantation, of foetal lateral ganglionic eminence from 5-8 donors into bilateral caudate nucleus and putamen in two patients showed viability of grafts.…”
Section: Cell Transplantation Provides An Improvement Of Symptoms Forsupporting
confidence: 83%
“…Integration of grafted tissue without clinical improvement 1 C a p e t i a net al 14 Stem cells and neurological diseases S Gögel et al additional immunosuppressive therapy as antibodies against foetal donor antigens were detected in patient's blood samples. 10 Similar results have been obtained in a separate study initiated by Kopyov and colleagues in Los Angeles. Post-mortem examination, 6 years after transplantation, of foetal lateral ganglionic eminence from 5-8 donors into bilateral caudate nucleus and putamen in two patients showed viability of grafts.…”
Section: Cell Transplantation Provides An Improvement Of Symptoms Forsupporting
confidence: 83%
“…Nonetheless, immune responses against the fetal tissue allografts were evident. In the study reported by Krystkowiak et al [23], 5 of 13 patients manifested alloimmunization to donor antigens within a few months after cessation of pharmacological immunosuppression. In this study, 1 patient showed obvious clinical and radiological signs of rejection that was reversed by pharmacological immunosuppression.…”
mentioning
confidence: 94%
“…In normal development, both striatal and nonstriatal precursors originate in the superficial layers and migrate ventrally and laterally to and through the underlying striatal primordium [21,22]. Although the lateral ganglionic eminence gives rise to mostly striatal [23] medium spiny neurons, the medial ganglionic eminence gives rise to globus pallidus and cortical interneurons, which are cells that can share the expression of several nominally striatal markers [24]. Yet medial ganglionic eminence components are also important for both the proper development of striatal structures, and for their functional integration [25].…”
mentioning
confidence: 99%
“…Recent studies have shown either the presence of anti-HLAs or inflammation [22,[105][106][107]. Krystkowiak et al [107] reported that as many as half of the HD patients had immunization develop against donor antigens during their phase II multi-center study of fetal neural transplants, with 1 patient showing full clinical, radiological, and biological symptoms of immune rejection. In that particular case, clinical status alteration was correlated with a decreased metabolic activity in the right striatum, accompanied by edema, as shown by magnetic resonance imaging and positron emission tomograhic scans.…”
Section: Immunogenicity Of Striatal Neural Graftsmentioning
confidence: 99%